2014
DOI: 10.1007/s11274-014-1712-2
|View full text |Cite
|
Sign up to set email alerts
|

Potent in vitro synergism of fusidic acid (FA) and berberine chloride (BBR) against clinical isolates of methicillin-resistant Staphylococcus aureus (MRSA)

Abstract: It was found in the present study that combined use of fusidic acid (FA) and berberine chloride (BBR) offered an in vitro synergistic action against 7 of the 30 clinical methicillin-resistant Staphylococcus aureus (MRSA) strains, with a fractional inhibitory concentration (FIC) index ranging from 0.5 to 0.19. This synergistic effect was most pronounced on MRSA 4806, an FA-resistant isolate, with a minimum inhibitory concentration (MIC) value of 1,024 μg/ml. The time-kill curve experiment showed that FA plus BB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…The most significant synergistic effects towards CoNS strains were noted when berberine was combined with linezolid, cefoxitin, and erythromycin [33]. In another study, the combined use of fusidic acid (FA) and berberine chloride (BBR) was found to result in an in vitro synergistic action against 7 out of 30 clinical methicillin-resistant Staphylococcus aureus (MRSA) strains [34]. In the present study, we examined the sub-MICs of berberine and sub-MICs of vancomycin for biofilm formation in C. difficile strains.…”
Section: Discussionmentioning
confidence: 99%
“…The most significant synergistic effects towards CoNS strains were noted when berberine was combined with linezolid, cefoxitin, and erythromycin [33]. In another study, the combined use of fusidic acid (FA) and berberine chloride (BBR) was found to result in an in vitro synergistic action against 7 out of 30 clinical methicillin-resistant Staphylococcus aureus (MRSA) strains [34]. In the present study, we examined the sub-MICs of berberine and sub-MICs of vancomycin for biofilm formation in C. difficile strains.…”
Section: Discussionmentioning
confidence: 99%
“…In traditional medicine, berberine has been widely used to treat bacterial diarrhea and gastroenteritis for a long history. Recently, berberine was demonstrated as a strong synergist for many commonly used antibiotics against clinical multi-drug resistant isolates of MRSA 8 9 10 . It is noted that sub-MICs of berberine exhibited significant synergistic effects on four conventional antimicrobial agents, including ampicillin (AMP), azithromycin (AZM), cefazolin (CFZ), and LEV 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, berberine has been demonstrated to be a strong synergist for antibiotics 5 6 . Synergistic interactions between berberine and commonly used antimicrobial agents exhibit therapeutic benefits against a broad spectrum of pathogenic microorganisms, including methicillin-resistant Staphylococcus aureus (MRSA) 7 8 9 10 . Many reports have shown that combined use of berberine improved the bactericidal activity of antibiotics against MRSA, lower the MICs of antibiotics, and notably decreased adhesion and intracellular invasion of MRSA 8 9 10 .…”
mentioning
confidence: 99%
“…It’s an isoquinoline alkaloid isolated from the rhizome, roots and stem bark of a number of Chinese herbs of Berberis species (Godugu et al, 2014, Ning et al, 2009). BBR presents various pharmacological activities such as antibacterial, antioxidant, cholesterol-lowering, and anti-inflammatory activities (Liang et al, 2014, Riccardi et al, 2001, Li et al, 2014, Kong et al, 2004, Choi et al, 2006). It also exhibits anticancer effects in a variety of cancer cells including glioblastoma, hepatoma, melanoma, colon, breast, prostate, oral, colorectal, lung, leukemia, and osteosarcoma (OGuamán Ortiz et al, 2014).…”
Section: Introductionmentioning
confidence: 99%